Carbothermal reduction of fayalite: Thermodynamic and non-isothermal kinetic analysis - Li Z.; Ma G.-J.; Zou J.-J.; Zheng D.-L.; Zhang X. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The present paper investigated the thermodynamics and kinetics of carbothermal reduction of fayalite by non-isothermal method combining with thermogravimetric analyzer and applying the Flynn-Wall-Ozawa (FWO) and Málek models. According to the thermodynamic analysis, the starting temperature of direct reduction reaction of fayalite was 806.79℃ in the standard state. The indirect reduction reaction could not take place in the standard state. While the volume percentage of CO was higher than 86 vol.% in nonstandard state, the indirect reduction could take place in the range of experimental temperature. Meanwhile, Boudouard reaction could promote the indirect reduction process. The kinetic analysis results showed that at the temperature below 1100℃, the main reduction reaction was the direct reduction between fayalite and graphite. With the temperature increasing, the fayalite reacted with CO generated from the gasification of graphite. When the reduction rate increased from 0% to 50%, the activation energy of the reaction increased to 524.41 kJ/mol. Then, the activation energy decreased with the increase of reduction rate. The carbothermal reduction of fayalite was a multistep reaction. The controlling step in the initial stage was the gasification of graphite. As the reaction proceeded, the generated CO provided a good kinetics condition for the carbothermal reduction of fayalite, and the controlling step of the reaction was the nucleation and growth of the metallic iron.